Factors Related to HIV/AIDS Prevention Behavior in Housewives - Arum Budiyati; Sri Rahayu; Ngadiyono Ngadiyono; Runjati Runjati (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
In 2017 there were 48,300 HIV cases in Indonesia and 9,280 AIDS cases. The cumulative AIDS cases in 1987-2017 were 102,667 cases, with the number of AIDS infections in housewives reaching 14,721 cases. The development of the HIV/AIDS epidemic in Indonesia since 2000 has continued to increase. Responding to these problems, it is necessary to prevent HIV/AIDS. The purpose of this study was to find out what factors were related to HIV/AIDS prevention behavior in Jatijajar Village, the working area of the Bergas Health Center, Semarang Regency in 2019. This is a quantitative research with correlational design. Proportionate Stratified Random Sampling is applied. Chi-square test shows there are relationships between the variables of education level (p-value 0.006), knowledge (p-value 0.027), attitude (p-value 0.007), and husband's support (p-value 0.006) with HIV/AIDS prevention behavior. There is no relationship between age (p-value 0.616) and husband's occupation (p-value 0.161) with HIV/AIDS prevention behavior among housewives in Jatijajar Village in 2019. There are relationships between education level, knowledge, attitude, and husband's support with HIV/AIDS prevention behavior in housewives. The variables most related to the HIV/AIDS prevention behavior variable were the level of education and husband's support. Knowledge of housewives about HIV/AIDS prevention needs to be increased, one of which is through socialization by health centers and other institutions related to HIV/AIDS to create healthy housewives.